Active stress field in central Italy: a revision of deep well data in the Umbria region - S. Pierdominici (Annals of Geophysics, 2008)
In this area the active stress from borehole breakout analysis shows a prevalent NE-SW extension, perpendicular to the main tectonic structures, in agreement with stress inferred from earthquake focal mechanisms and with the strain velocity field. A detailed analysis of active stress data allows to infer the influence of active structures on the local stress field orientations. San Donato 1 well shows a minimum horizontal stress orientation N55±22°, in agreement with the regional trend and with the local one influenced by its vicinity to the Alto Tiberina Fault. Whereas Monte Civitello 1 well shows a quite different orientation, N12±29°, due to its different location, more to the east, and to the structures that it crosses. Although the angular difference between the two directions is within the error, to estimate the regional active stress field many borehole data should be analysed or smoothing maps should be evaluated. In fact, each borehole dataset could be influenced by local stress conditions that in some case can be different from the regional trend. The two breakout orientations perfectly depict the regional extension along the axis of the Apennines and also the minimum horizontal stress rotation moving eastward to the area where compression is predominant.